Effects of Resistance Training Periodization on Power Output and Sprint Performance in Track Athletes - Idrees Saad Mahmood (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2026)
The purpose of this study was to determine the effect of resistance training periodization on power output and sprint performance in a cohort of track athletes. The researchers employed an experimental design—repeated measures. There were twenty male (100 m, 200 m, and 400 m) track athletes that took part in the study. The participants completed an 8-week periodized program utilising resistance training consisting of three sessions per week progressing from maximal strength development to strength–power conversion. Performance variables included countermovement jump (CMJ), peak power, 10 m and 30 m sprint time, and force–velocity profile indicators (F0, V0, and Pmax). Pre- and post-tests were conducted under controlled conditions. For statistical analyses, paired-samples t-tests were performed, and significance was set at p ≤ 0.05; effect sizes (Cohen’s d) were also calculated. Consequently, the authors found that all variables improved, with CMJ height and CMJ peak power increasing 11.76% and 10.29%, respectively, highlighting an improvement in lower-limb explosive power. Sprint performance was significantly improved (4.40% and 3.74% reductions in 10 m and 30 m sprint times, respectively). There were positive adaptations according to the force–velocity profile variables, with F0 (+7.48%), V0 (+3.91%), and Pmax (+9.75%) values all increasing. The authors reported that the effect sizes were mostly large. In conclusion, our findings indicated that periodized resistance training increased both power output and 10m sprint times in track athletes. Progressively transitioning from maximal strength to explosive power appears to be an effective approach to enhance neuromuscular adaptations and sprint-specific performance in this population. As such, periodized resistance training should be integrated within sprint training programs to optimize athletic performance.